Blood flow restriction and cuff width: effect on blood flow in the legs. (21st January 2018) - Mouser, J. Grant; Dankel, Scott J.; Mattocks, Kevin T.; Jessee, Matthew B.; Buckner, Samuel L.; Abe, Takashi; Loenneke, Jeremy P.
Summary: Much of the literature examining blood flow restriction in the lower body uses cuffs of differing widths. It is currently unknown whether similar relative pressures using cuffs of differing widths elicit the same blood flow response. Purpose: To examine the hemodynamic responses to relative pressures using two commonly used cuffs (10 and 12 cm). Methods: In a random order over two laboratory visits, one cuff was applied to the right proximal thigh of the participant (men = 17, women = 14), and arterial occlusion pressure (AOP) was measured. Ultrasound measures of blood flow, mean blood velocity, peak blood velocity and artery diameter were taken from the posterior tibial artery at rest and during the application of 10% increments of the AOP. Results: There was no significant difference between the 10‐ and 12‐cm cuff relating to blood flow (−0·501 ml min −1, SD 7·9, P  = 0·728), mean blood velocity (−0·168 cm s −1, SD 1·7, P  = 0·590), peak blood velocity (0·586 cm s −1, SD 11·7, P  = 0·783) or artery diameter (0·003 cm, SD 0·02, P  = 0·476). There was a main effect of pressure for blood flow ( P <0·0005), mean blood velocity ( P <0·0005), peak blood velocity ( P <0·0005) and artery diameter ( P  = 0·005), with each decreasing with increasing pressures. Peak blood velocity increased to 60% of AOP before decreasing with increased pressure. Conclusion: As long as relative pressures are applied, cuff width appears to have little to no effect on the blood flow stimulus during blood flow restriction at rest.